198 ETS-1 AND P300 SYNERGISTICALLY UP-REGULATE NATRIURETIC PEPTIDE RECEPTOR A GENE (NPR1) TRANSCRIPTION. Issue 1 (1st January 2007) - Kumar, P.; Pandey, K. N.
Abstract : Activation of guanylyl cyclase/natriuretic peptide receptor A (GC-A/NPRA) produces the second messenger cGMP, which plays a pivotal role in maintaining blood pressure and cardiovascular homeostasis. Studies to elucidate the molecular regulation of Npr1 (coding for NPRA) gene transcription are limited. The present study was conducted to elucidate the molecular mechanism governing Npr1 gene transcription, which would provide new insights into strategies to control NPRA-dependent signaling in pathophysiology of hypertension and cardiovascular disorders. Npr1 promoter-reporter deletion constructs were transiently transfected in mouse mesangial cells (MMCs) and transcriptional activity was measured by dual luciferase assay. To determine the effect of transcription factors, cotransfections were performed along with the promoter constructs. Functional deletion analysis of Npr1 promoter defined a ≈400 base pairs (bp) region as a basal promoter having Sp1, Lyf-1, p300, c-ETS, and GATA 1/2 transcription factor binding sites. Further deletion of the basal promoter defined a 90 bp fragment as core promoter, having two Ets-1 and a p300 binding motifs, which was found to be essential in controlling transcription. Electrophoretic mobility shift assay, competition binding, and supershift analyses confirmed that endogenously expressed Ets-1 binds to Ets-1 consensus sites. Site-directed mutagenesis of the two Ets-1 and p300 binding sites significantly reduced the functional activity ( p < .001) of Npr1 promoter. Overexpression of Ets-1 and p300 synergistically activated Npr1 core promoter activity by almost 16-fold ( p < .001), thus confirming the involvement of these transcription factors in mediating gene expression. Moreover, Ets-1 and p300 were found to be physically associated in MMCs by coimmunoprecipitation assay. In conclusion, Npr1 gene expression underlies a complex regulation in which Ets-1 activates and functions cooperatively with p300 to promote Npr1 gene transcription. Results from these studies will greatly help to understand the role of Npr1 gene expression and its function in the control of hypertension and cardiovascular regulation.